1971
DOI: 10.1136/bmj.3.5770.338
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the Breast-fed Infant to Gastroenteritis

Abstract: SummaryFrom in-vitro studies of breast and cow's milk preparations, and of the faeces from breast-fed and bottle-fed infants, a number of factors seemed likely to influence the production and maintenance of a lactobacillary flora and low pH in the faeces of newborn infants. These were mainly attributable to the nature of the feed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
4

Year Published

1975
1975
1994
1994

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(89 citation statements)
references
References 9 publications
8
77
0
4
Order By: Relevance
“…The results of earlier studies (Bullen and Willis, 1971) are in general agreement with the observations and conclusions of Ross and Dawes (1954). Breastfed infants produce an acidic environment in the lumen of the large intestine, and acetic acid is frequently present as an acetate buffer (Bullen, Tearle and Willis, 1976).…”
supporting
confidence: 81%
“…The results of earlier studies (Bullen and Willis, 1971) are in general agreement with the observations and conclusions of Ross and Dawes (1954). Breastfed infants produce an acidic environment in the lumen of the large intestine, and acetic acid is frequently present as an acetate buffer (Bullen, Tearle and Willis, 1976).…”
supporting
confidence: 81%
“…Isolation rates and concentrations of veillonellas as high as this have been previously described only in breast-fed Guatemalan infants from about 5 weeks of age (Mata & Urrutia, 1971). Bullen & Willis (1971) have provided experimental evidence which suggests that the inter-relationships between E. coli and anaerobic lactobacilli are governed by the relative lactose, phosphate and protein concentrations and relative buffering capacities of breast and artificial milks. Differences in the concentrations and metabolic activities of human faecal bacteria have been described in adults from different geographical areas and these have been related to the effects of differing diets (Hill et al 1971).…”
Section: Discussionmentioning
confidence: 64%
“…However, Mata & Urrutia (1971) showed that in breast-fed babies it is towards the end of the first week of life that the E. coli count begins to fall relative to the Lactobacillus bifidus count and possibly this study took place too early in the neonatal period to show a difference in the faecal coliform counts between breast-and bottle-fed babies. Moreover, many of the hospital breast-fed babies received a bottle feed during the night and there is evidence (Bullen & Willis, 1971;Bullen, Tearle & Stewart, 1977;Bullen, Tearle & Willis, 1976) that such babies have a faecal flora resembling that of bottle-fed babies. The home breast-fed babies who received no supplements had slightly but not significantly lower coliform counts than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…1974; Noy, Ayliffe & Linton, 1974; Gothefors, Olling & Winberg, 1975;Hewitt & Rigby, 1976) or older children at home (Moorhouse, 1969;Mata & Urrutia, 1971;Linton et al 1972;Ellis-Pagler, Crabtree & Lambert, 1975). Although the work of Bullen & Willis (1971) was on babies that were delivered at home and in hospital, only the effects of breast and bottle feeding on the faecal flora were considered. In this investigation we compare the faecal flora of babies in both environments taking into account the type of feed given.…”
Section: Introductionmentioning
confidence: 99%